Intensive dairy farming systems from Holland and Brazil: SWOT analyse comparison - Rodrigo Augusto Cortêz Passetti (Acta Scientiarum. Animal Sciences, 2016)
Intensive systems of milk production in Brazil and Holland are compared by SWOT analysis. Twenty-one farms, 10 in Wageningen, central region of Holland, and 11 in Castro, central-eastern region of the state of Paraná, Brazil, were sampled. Data were retrieved from semi-structured interviews with the owners or people responsible for dairy activities, using a questionnaire guide and a digital recorder. After results were analysed, a table was elaborated representing the strengths, weaknesses, opportunities and risks for each country. Dairy farms in Holland were uniform, or rather, small and medium-sized farms with high production. It has also been observed that Dutch farms have several problems due to high intensification, for example, hoof diseases with great economic loss. In the case of Brazilian dairy farms, several types of systems and degrees were detected. Brazilian production in the region analysed features a higher quantity than that in Holland, with less intensity when compared to that on Dutch farms.